Digital Era Islamic Education Policy: Formalizing Coding and AI Curricula at MA Mambaul Ulum - Muhammad Haidir Ali; Abdussomad Abdussomad (Divisi Penelitian dan Pengabdian Masyarakat Yayasan Cerdas Pedia Indonesia, 2026)
The rapid integration of Artificial Intelligence within Islamic education frequently triggers sociological and religious tensions concerning secular technological determinism. This study investigates the institutionalization of algorithmic curricula at Madrasah Aliyah Mambaul Ulum, Indonesia. Utilizing a descriptive analytical qualitative case study, primary data were gathered through interviews, observations, and document analysis. Findings were examined using the Ritzer Integrative Sociological Paradigm and Islamic jurisprudence. Results reveal a coherent dialectic between macro subjective theological legitimacy and macro objective bureaucratic regulation. This policy is validated by micro objective system efficiency and micro subjective cultural adaptations that transform technological anxiety into academic confidence. The research refutes secular determinism, demonstrating that algorithmic infrastructures can be subordinated to Islamic epistemological frameworks to strengthen pedagogical authority. Ultimately, this localized initiative formulates a transnational governance model for the decolonization of digital knowledge. This ensures digital sovereignty for global Muslim educational institutions without compromising their foundational ontological and spiritual roots.